Beyond Men's Experiences: Developing a Psychometric Scale to Measure Perceptions of Men's Fitness for Professional Nursing - Smith, Christopher Michael (East Carolina University, 2022)
Background: According to the 2021 United States (U.S) Bureau of Labor Statistics, men represent only 13% of Registered Nurses in the U. S. This minority portion of the workforce has been extensively explored through qualitative research studies. Men have indicated they feel unwanted and perceived as unfit for nursing. The purpose of this study was to quantify perceptions of men’s fitness for nursing, which was accomplished by developing and testing psychometric properties of the Fitness in Nursing Scale – Men (FiNS-M©) to quantitatively measure perceptions of men’s fitness for nursing. Methods: This study was guided by social role theory and employed a cross-sectional descriptive design. Scale development was informed by a systematized literature review. Chain referral sampling was used to recruit participants, (N = 635) through professional nursing organizations and nursing groups on multiple social media platforms respectively. Participants were asked to complete a survey during which they indicated their level of agreement with statements pertaining to men in nursing. Data were analyzed in R using confirmatory factor analysis (CFA) and multiple group confirmatory factor analysis to model data. Results: The final model was a unidimensional latent variable model that loaded on 25 items indicating men’s fitness for nursing. The model had good fit to the data, 2 (273, N = 635) = 964.55, RMSEA = .053, 90%CI [.049,.058], SRMR = .036 CFI = .940, TLI = .934. Configural, metric, and scalar invariance held. Scale scores across groups were not significantly different, Δ2 (1) = 0.93, p = .335, for women (M = 5.94) compared to men (M = 5.99). Conclusion: This was a novel study that provides valuable data and insight into men in the nursing workforce. Results suggested that both women and men “agree” that men are fit for nursing. Future research will be aimed at continuing exploration in this area of inquiry by testing additional multiple group models and conducting multi-level analyses, in hopes of strengthening the nursing workforce by using findings to guide recommendations for change. Recommendations should be aimed at improving nursing culture and diversity in the workplace for all nurse clinicians and academic faculty.
Keywords: men in nursing; gender; nurses; quantitative; Psychometrics; Men's Health; Male; Exercise